Beyond human rights: the legal status of the individual in international law - Peters, Anne (Cambridge studies in international and comparative law, 2016)
The starting point for this study is the observation that with increasing frequency, international legal norms directly address and engage individuals. For instance, individual rights under international law appear to arise from extradition treaties, treaties of friendship and establishment, double taxation agreements, transport treaties, intellectual property treaties, investment protection treaties, treaties on the legal status of foreigners, and the Vienna Convention on Consular Relations. On the side of duties, the criminal responsibility of individuals under international law has in recent decades been fleshed out by the work of the ad hoc criminal tribunals and the International Criminal Court".
Updated and revised English version of: Jenseits der Menschenrechte
Hier auch später erschienene, unveränderte Nachdrucke
Literaturverzeichnis: Seite 556-590
Keywords: Völkerrecht; Rechtsstellung; Individuum; Völkerrechtssubjekt; Individualrecht; Rechtsfähigkeit